Multifunctional steam floor / Aina Najwa Yaacob - Yaacob, Aina Najwa (2022)
Philips is one of the largest electronic company that focusing on the Personal Health (formerly Philips Consumer Electronics and Philips Domestic Appliances and Personal Care), Connected Care, and Diagnosis & Treatment (formerly Philips Medical Systems). In this company analysis, it is focusing on Sweep and Steam Cleaner produced by the Philips to be research and analysed about their current problems and come out with the solutions. The first problem regarding their product is do not have variations size of nozzle cleaning. It only have one size of nozzle that quite in a big size. The small and narrow places cannot be clean properly because the nozzle cannot reach to do cleaning and steaming. As for the next problem is their product has small water tank which is 450 ml. It only can manage 20 minutes of steaming before they need refilling. This small tank only allow small space area for cleaning jobs and need to be refilling water often once it dry. With this way, users need to do extra works because keep on refilling the water tank until their cleaning works is done and will waste their time. Aside from that, there are few solutions to that which is do innovation by adding few more size of nozzles that will make consumer’s house can be clean and steam all places includes small and narrow places. The next solutions is upgraded tank capacity size more than 2 litres so that users will continues cleaning house with the product up to 2 hours which is the enough time to clean the whole house. All of these solutions are considered to upgrade quality product of Philips in order to make the company growth well.